The politics of cultural differences : social change and voter mobilization strategies in the post-New Deal period - Leege, David C. (Princeton : Princeton University Press, 2002)
How did Republicans manage to hold the White House through much of the past half century even as the Democratic Party held the hearts of most American voters? The authors of this groundbreaking study argue that they did so by doing what Democrats have also excelled at: triggering psychological mechanisms that deepen cultural divisions in the other party's coalition, thereby leading many of its voters either to choose the opposing ticket or to stay home.
Part I: Cultural theory and recent American politics. Anomalies of post-New Deal politics ; The political mobilization of cultural differences ; General components of cultural theory in political conflict ; Election rituals, ideological movements, and group politics ; Psychological mechanisms and campaign strategies. -- Part II: Case studies of the political mobilization of cultural differences. Cultural strains in the New Deal coalition ; A methodology for assessing cultural politics ; Keeping America purposeful, powerful, and pure ; Race and the transformation of the contemporary party system ; Gender, religion, and the second party transformation ; Cultural politics: some conclusions and practical implications.
Includes bibliographical references (pages 271-282) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Republican Party (Etats-Unis) -- 1945-.; Voting -- United States; Voting research -- United States; Politics and culture -- United States; Social choice -- United States; Vote -- États-Unis.; Sociologie électorale -- États-Unis.; Politique et culture -- États-Unis.; Choix collectif -- États-Unis.; POLITICAL SCIENCE -- Political Process -- General; POLITICAL SCIENCE -- Political Process -- Elections; Politics and culture; Social choice; Voting; Voting research; United States; Kulturpolitik; Kulturtheorie; Politischer Wandel; Sozialer Wandel; Wahlverhalten; USA; Politik; Wahl; Sociologie électorale -- États-Unis -- 1945- ...; Politique et culture -- États-Unis.; Psychologie politique -- 1900-1945.